Anthropometric Study of Orbitonasal Proportion and Their Comparisons in Bangladeshi Buddhist Rakhain Ethnic Males and Females - Iqbal, Mohammed; Nahar, Nazmun; Rahman, Kazi Md. Shahidur; Sultana, Nishat; Hossain, Shahana; Yeasmin, Farida; Uddin, SK. Amin Mohi (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Anthropometric pattern of the orbitonasal proportion varies with no universal normative values. Objective: The purpose of the present study was to evaluate the anthropometric study of orbitonasal proportion and their comparisons in Bangladeshi Buddhist Rakhain Ethnic males and females. Methodology: This cross-sectional study was carried out in the Department of Anatomy, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh from January 2011 to December 2011 for a period of one (01) year. Adult healthy Bangladeshi Buddhist Rakhain males with the age group of 18 to 30 years were included as study population. Standard of normative facial anthropometric values related to intercanthal distance and nose width. Results: This study shows the inner intercanthal distance (IICD) mean value of males and females as 33.19±2.88 mm and 31.28±2.78 mm, respectively with a statistically significant relationship (P<0.05). The nose width was 41.16 (±3.03) in male and 36.11 (±2.20) in female which was statistically significant (P<0.05). Conclusion: This study shows that intercanthal distance and nose width differs across the adult healthy Bangladeshi Buddhist Rakhain males and females. Gender and ethnicity are two of the main parameters that affect the variation. These findings would be applicable in clinical setup as reference values during surgical planning. Journal of National Institute of Neurosciences Bangladesh, January 2024;10(1):21-25